2006
DOI: 10.1080/00288306.2006.9515185
|View full text |Cite
|
Sign up to set email alerts
|

Olistostromes marking tectonic events, East Coast, New Zealand

Abstract: Three discrete, successive tectonic events are marked by olistostromes in the East Coast, North Island. An Eocene Mataikona event is characterised by in situ dismembered beds. A second, Owahanga event is Otaian and preceded wrench faulting coeval with the start of oblique subduction at the East Coast margin. This second event is characterised by extended emplacement of exotic material followed by gliding, gravity-driven nappes that are probably related to obduction along the north coast of the North Island. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Our estimates of the accelerated cooling phase in the hanging wall of the subduction zone concur with the period of increased crustal deformation during the late Oligocene to early Miocene, e.g., the development of thrust belts (~25–20 Ma) in eastern North Island [ Chanier and Ferriere , ; Rait et al ., ] and allochthon obduction in Northland and the East Cape (~25–21 Ma) [ Ballance and Spörli , ; Spörli , ]. The accelerated basement unroofing increased the sediment flux into the adjacent basins, depositing flysch sequences into the East Coast Basins to the east of the proto‐Axial Ranges [ Delteil et al ., ; Lee et al ., ]. In northeastern North Island, terrestrial conglomerates (in the early Miocene Tolaga Group) were suggested to derive from local emergent landmass, which had been uplifted during the subduction initiation [ Marsaglia et al ., ].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Our estimates of the accelerated cooling phase in the hanging wall of the subduction zone concur with the period of increased crustal deformation during the late Oligocene to early Miocene, e.g., the development of thrust belts (~25–20 Ma) in eastern North Island [ Chanier and Ferriere , ; Rait et al ., ] and allochthon obduction in Northland and the East Cape (~25–21 Ma) [ Ballance and Spörli , ; Spörli , ]. The accelerated basement unroofing increased the sediment flux into the adjacent basins, depositing flysch sequences into the East Coast Basins to the east of the proto‐Axial Ranges [ Delteil et al ., ; Lee et al ., ]. In northeastern North Island, terrestrial conglomerates (in the early Miocene Tolaga Group) were suggested to derive from local emergent landmass, which had been uplifted during the subduction initiation [ Marsaglia et al ., ].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Delteil et al . (2006) described three olistostromes that marked successive tectonic events in the deformed belt of the North Island, New Zealand during Cenozoic time. The oldest shows seafloor instability and the other two were connected with nappe emplacement and strike-slip faults.…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence interval of olistostromes in the geological record may be unrevealed with varying 751 degrees of accuracy, based on the well-constrained timing of olistostrome emplacement, subsequent 29 tectonic deformation events, and metamorphic history of the depositional environment of 753 olistostromes. Although the emplacement of an each single gravitational body is an instantaneous and 754 episodic event, the recurrence time for olistostrome and olistolith emplacement may vary from 755 thousands of years to several millions of years (e.g., Scherba, 1985;Delteil et al, 2006;Graziano, 756 2001;Wise and Ganis, 2008;Camerlenghi and Pini, 2009;Festa et al, 2015c). This time-scale may 757 be strongly affected by the duration of each regional-scale, single tectonic event, or more specifically 758 by the combination of eustatic and geodynamic processes (e.g., sedimentary transgressive -759 regressive cycles, global climate changes, gas-hydrates dissociations).…”
mentioning
confidence: 99%